Kekerasan berbasis gender dalam kasus perceraian pada masa pandemi Covid-19 di Kabupaten Cirebon - Naila Farah; Musahwi Musahwi; Muhamad Ridho Hidayatullah (Yinyang: Jurnal Studi Islam Gender dan Anak, 2023)
Divorce cases during the Covid-19 Pandemic experienced a significant increase. In Cirebon Regency, an increase in the divorce rate was followed by many cases of violence against women in the family environment during the 2020-2023 Pandemic. This research seeks to understand the problem of gender-based violence in divorce cases and the various psycho-social implications arising from this condition for victims. In order to analyze the problem comprehensively, this study uses the framework of structural violence, cultural violence, and direct violence (physical and symbolic). Based on the results of the description and theoretical analysis, this study yielded findings including: (1) victims of violence were experienced by families with a weak economic basis, coming from poor families; (2) victims experience physical, psychological, sexual violence and neglect of the household; (3) the victim chooses a divorce to escape violence rather than asking for protection from women's protection services; (4) victims experience multiple psycho-social pressures after violence and divorce, namely: as victims of domestic violence, unemployment and economic instability, as well as the burden of raising children without the perpetrator's responsibilities as a father.